Koagulopati pada Pasien COVID-19 - Isfandiary, Annisa; Ismandiya; KSS, Nurita Dian; Redjeki, Ike Sri (Jurnal Komplikasi Anestesi, 2020)
The pathogenesis theory of COVID-19 is still developing. While there are lot of theory coming up, the spotlight mostly reveal on inflamation, coagulopaty, and thrombo-infalamation. We reported an 53 years-old man arrived at the hospital with confirmed COVID-19, severe pneumonia and hypercoagulability state. Patient was referred to Hasan Sadikin Hospital and treated at COVID-19 isolation room, with the used of ventilator for 21 days. Further laboratory test found thromboelastrograph hypercoagulation from elevating level of fibrinogen and thrombocyte. SARS-CoV-2 enter host cells and cause a disruption of both epithelial and endothelial cells together with an alveolar inflammatory cell infiltrate leading to high levels of early response-proinflammatory cytokines. In severe COVID-19 patients, this immune response is excessive and thus described as a systemic “cytokine storm”. It is responsible for endotheliopathy and hypercoagulability state, leading to both systemic and macrothrombosis and microthrombosis. In this case we found hypercoagulation in thromboelastograph with increased D-dimer and fibrinogen, so that the patient was diagnosed with hypercoagulopaty Patient was given therapy of heparin. After heparin therapy patient had an improvement of clinical symptoms and laboratory result.